Multiomics analysis revealed miRNAs as potential regulators of the immune response in Carassius auratus gills to Aeromonas hydrophila infection - Huo, Jiaxin; Hu, Xiucai; Bai, Jie; Lv, Aijun (Frontiers in Immunology, 2023)
The gill of fish is an important immune organ for pathogens defense, but its miRNAs expression and regulatory mechanism remain still unclear. Here, we report the histopathological and immunohistochemical features in gills of crucian carp Carassius auratus challenged by Aeromonas hydrophila, and the small RNA libraries for gills were constructed and sequenced on the Illumina HiSeq 2000 platform. A total of 1165 differentially expressed miRNAs (DEMs) were identified in gills, of which 539 known and 7 unknown DEMs were significantly screened (p< 0.05). GO and KEGG enrichment analysis revealed that potential target-genes/proteins were primarily involved in 33 immune-related pathways, in which the inflammatory responses were focused on, such as TLR, MAPK and NF-κB signaling pathways. Moreover, the expression levels of 14 key-miRNAs (eg., miR-10, miR-17, miR-26a, miR-144, miR-145, miR-146a) and their target-genes (eg., TNFα, TLR4, NF-κB, TAB1, PI3K, IRAK1) were verified, as well as the iTRAQ protein levels were significantly associated with qRT-PCR analysis (p< 0.01). The miR-17/pre-miR-17 in the regulation expression of NF-κB target-gene was identified, and phylogenetic tree analysis showed that pre-miR-17 of C. auratus with the closest similarity to zebrafish Danio rerio was highly conserved in teleosts. This is firstly reported on multi-omics analysis of miRNAs and proteins in the gills of C. auratus infected with A. hydrophila, thus enriching the regulation mechanism of local immune response in Cyprinidae fish.